A Reply to John Dudley on Aristotle, Physics 2.5, 196b17 - Giardina, Giovanna R. (Peitho. Examina Antiqua, 2017)
In this article, I restate the interpretation of Aristotle’s Ph. 2.5, 196b17–21, which I presented for the first time in my book I fondamenti della causalità naturale (2006). According to my reading, both the things that are due to deliberation and those that are not (Arist. Ph. 196b17–18) fall within the group of beings which come to be not for the sake of anything (Arist. Ph. 196b17). In his recent book, Aristotle’s Concept of Chance (Albany 2012), John Dudley found my interpretation laudable and original but rejected it, opting for the traditional interpretation. As he did not provide sufficient reasons for this, I deem it appropriate to discuss more broadly and in greater detail my interpretation in order to demonstrate that it is correct theoretically, linguistically and grammatically. I also discuss a reading of Neoplatonic commentators which seems to me very useful: when commenting on Aristotle, they start with a very prejudicial interpretation which comes from Alexander and which probably determined all later interpretations of the passage. According to this interpretation, beings which come to be not for the sake of anything (Arist. Ph. 196b17) are beings that have no teleology of any kind. Yet this exegetic position faces a series of difficulties which can easily be solved if one assumes, as I do, that these beings have a certain end albeit not an intrinsic one.